Influence of Business Communication on Organizational Performance of Nepalese Enterprises - Basnet, Utsav (Nepalese Journal of Economics, 2025)
This study examines the influence of business communication on organizational performance of Nepalese enterprise. Organizational performance is selected as the dependent variable. Similarly, new business ideas, verbal communication, network communication, effective communication and two-way communication are selected as the independent variables. This study is based on primary data with 121 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing organizational performance of Nepalese enterprise. The study showed that a new business idea has a positive impact on organizational performance. It means that increase in new business ideas leads to increase in consumer organizational performance. Similarly, verbal communication has a positive impact on organizational performance. It indicates that increase in verbal communication leads to increase in organizational performance. Moreover, network communication has a positive impact on organizational performance. It means that increase in network communication leads to increase in organizational performance. Likewise, effective communication has a positive impact on organizational performance. It shows that increase in effective communication leads to increase in organizational performance. Further, two-way communication has a positive impact on organizational performance. It shows that higher the two-way communication, higher would be the organizational performance.